2013
DOI: 10.1166/jbn.2013.1667
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Patterned Nanowire Surfaces Encourage Directional Neural Progenitor Cell Adhesion and Proliferation

Abstract: Peripheral nerve damage is common in the United States, with an estimated 200,000 patients treated surgically each year. Autografts, the current gold standard treatment, require that the patient trade functionality by transplanting a nerve from elsewhere in the body. For this reason, tissue-engineering scaffolds that can regenerate nervous tissue and that can direct proliferation need to be investigated. In this work we investigated the influence of micro-patterned nanowire surfaces on neuronal progenitor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Similar results have been found for other tissues within the hand, such as cartilage, muscle, blood vessels, nerve and skin (Bayati et al, 2013;Bechara and Popat, 2013;Wu et al, 2014;Yildirimer et al, 2012). For example, surface modifications of chitosan scaffolds using cell-recognition motifs, attachment domains recognized by cells, have been shown to stimulate chondrogenesis by enhancing proliferation of chondrocytes (Kuo and Wang, 2011).…”
Section: Scaffold Topographies In Hand Tissue Engineeringsupporting
confidence: 73%
“…Similar results have been found for other tissues within the hand, such as cartilage, muscle, blood vessels, nerve and skin (Bayati et al, 2013;Bechara and Popat, 2013;Wu et al, 2014;Yildirimer et al, 2012). For example, surface modifications of chitosan scaffolds using cell-recognition motifs, attachment domains recognized by cells, have been shown to stimulate chondrogenesis by enhancing proliferation of chondrocytes (Kuo and Wang, 2011).…”
Section: Scaffold Topographies In Hand Tissue Engineeringsupporting
confidence: 73%
“…Their experimental results indicated that micro/ nanohybrid structures could affect the morphology of cells and promote cell differentiation. 22 Materials with micro/ nanostructures can modulate the specific expression of neural cells such as neuronal polarity, axon guidance, synaptogenesis, and electric transductions. 19,20,23,24 In this study, we propose a novel conduit that mimics the natural structure and environment of neural cells to effectively guide the growth of regenerating neural cells.…”
Section: Introductionmentioning
confidence: 99%
“…Even though cell colonies became twofold after 5 days in comparison with NSCs cultured on PCL and nanowire. These data added a notion that fabrication of nanotopographical regions in distinct substrates with hard, smooth, and hydrophobic consistency could dictate and direct cell fate (Figure2w) 54,55. In addition to the effect of micro and nano-sized dimensions on the induction of specific phenotypes in cultured cells, the combination of this modality with other approaches could improve the efficiency of phenotype acquisition in cultured NSCs.…”
mentioning
confidence: 95%